CITISPACE-BASED VISUALIZED ANALYSIS OF RESEARCH ON CHINESE EFL LEARNERS’ ORAL ENGLISH OUTPUT IN RECENT FIFTEEN YEARS - Shen, Tiantian; Hu, Weijie (Universitas Islam Sumatera Utara, 2025)
Oral English output is a core link in the transformation of linguistic knowledge into practical application ability. Taking the China National Knowledge Infrastructure (CNKI) academic journal network publishing database as the data source, this paper uses the CiteSpace 6.3.R 1 data visualization software to map scientific knowledge, and conducts a systematic analysis of relevant literatures in the field of Chinese EFL learners' oral English output over the past 15 years, so as to reveal the development trends, hotspots and frontiers of this field. The results show that the research in the field of Chinese EFL learners' oral English output from 2010 to 2025 presents a fluctuating characteristic, going through three stages: the accumulation and development stage, the significant growth stage and the stable maturity stage. Research hotspots focus on oral English output, with emphasis on English teaching practice in different school stages; research frontiers concentrate on the cultivation of oral English output ability in specific school stages. Future research should, on the basis of diversifying research methods, carry out studies around different themes, promote interdisciplinary research, and conform to the development of educational digitalization.